Etnisitas dan Konservatisme Akuntansi pada Perusahaan Publik di Indonesia - Setiawan, Antonius Singgih; Fransysca, Ellen (Jurnal Kajian Akuntansi, 2020)
AbstractAccounting conservatism is debated in practice, literature, and financial accounting research. The principle of conservative accounting is considered as an action to control the optimistic behavior of management and business owners but the potential to cause biased information. This study aims to examine the influence of ethnicity of authorized officials in the publication of corporate financial statements on accounting conservatism in public companies in Indonesia. A total of 71 samples of manufacturing companies listed on the IDX in 2019 and fulfilling sampling criteria were used to test the hypothesis. The research data were analyzed using independent sample t-test. The results showed that the difference in the ethnicity of the official level in the company's financial reporting would affect the level of accounting conservatism in a company. Pribumi ethnicities with general characteristics as ethnicities that prioritize stability in their business tend to have higher conservatism characteristics compared to Tionghoa ethnic groups who tend to be more willing to take risks in their every decision. An important implication of the results of this study is that the authorized officials in publishing the company's financial statements must be able to control their conservative principles.Keywords: Accounting conservatism; Ethnicity; Manufacturing sector; Pribumi ethnic; Tionghoa ethnic.AbstrakKonservatisme akuntansi menjadi perdebatan dalam praktik, literatur dan penelitian akuntansi keuangan. Prinsip konservatisme akuntansi dinilai sebagai tindakan untuk mengendalikan perilaku optimistis manajemen dan pemilik usaha namun berpotensi menimbulkan informasi yang bias. Penelitian ini bertujuan untuk menguji pengaruh etnisitas pejabat yang berwenang dalam pemublikasian laporan keuangan perusahaan terhadap konservatisme akuntansi pada perusahaan publik di Indonesia. Sebanyak 71 sampel perusahaan manufaktur yang terdaftar di BEI tahun 2019 dan memenuhi kreteria sampling digunakan untuk menguji hipotesis. Data penelitian di analisis menggunakan independent sample t-test. Hasil penelitian menunjukkan bahwa perbedaan kelompok etnisitas pejabat yang berwenang dalam pelaporan keuangan perusahaan akan berpengaruh pada tingkat konservatisme akuntansi di suatu perusahaan. Etnis Pribumi dengan karakteristik umum sebagai etnis yang lebih mengedepankan sifat stabil dalam berusaha cenderung memiliki sifat konservatisme yang lebih tinggi dibandingkan dengan kelompok etnis Tionghoa yang cenderung lebih berani ambil risiko pada setiap keputusan mereka.  Implikasi penting dari hasil penelitian ini adalah para pejabat yang berwenang dalam pemublikasian laporan keuangan perusahaan harus dapat mengendalikan prinsip konservatime mereka.Kata Kunci: Etnisitas; Etnis Pribumi; Etnis Tionghoa; Konservatisme akuntansi; Sektor manufaktur.